Protective roles of empathy and compassion against loneliness early in the SARS-CoV-2 pandemic - Melissa M. Karnaze; Cinnamon S. Bloss (Current Research in Behavioral Sciences, 2023)
Importance: The SARS-CoV-2 pandemic has caused concern of an impending “second wave” of loneliness and mental health problems following social disruption that included mandates to physically and socially distance from others. Research is needed to identify factors that can mitigate loneliness, which results from perceptions that one's social connections are less than desirable. Objective: We examined whether individual differences in empathy and compassion would predict loneliness in a large sample of adults surveyed early in the SARS-CoV-2 pandemic controlling for social desirability and loneliness risk factors. Design: Using a cross-sequential design, a baseline survey was fielded at seven time points (every two weeks) to seven different cohorts from March 22 to June 15, 2020. For each cohort, a follow-up survey was fielded one month after each baseline survey. Participants: Participants who comprised the seven cohorts were recruited from two U.S. convenience samples, Amazon Mechanical Turk and Qualtrics Online Panels. The response rate across the follow-up surveys was 59% (total N = 3262). Main outcomes and measures: We hypothesized that dispositional empathy and compassion at baseline would be associated with lower levels of loneliness at one-month follow-up. Results: Higher empathy at baseline (Beta = -0.03; 95% CI -0.05 to -0.02; P < .001) was associated with lower loneliness at follow-up, even after controlling for social desirability and other loneliness risk factors. Higher compassion at baseline (Beta = -0.03; 95% CI -0.05 to -0.01; P < .001) was also associated with lower loneliness at follow-up. Conclusion and relevance: We found that early in the SARS-CoV-2 pandemic, higher levels of empathy and compassion predicted lower levels of loneliness one month later. Future research, including experimental designs, should examine whether increasing empathy, or the tendency to share others’ positive and negative feelings, can confer a protective effect against perceived social isolation during collective trauma characterized by physical and social distancing.